PELAYANAN KOMUNIKASI PERPUSTAKAAN DAN ARSIP DAERAH DI KABUPATEN PANDEGLANG - Pipin Patimah (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2022)
AbstractCommunication services are a must that is consistent and a clear commitment that has the value of progress in improving public services, so that visitors feel a good guarantee of comfort, from all functional libraries. This research is a qualitative descriptive research. Is a study that is intended to collect information about the status or symptoms that exist, namely the state of symptoms that are collected in the field according to what they are at the time the study is carried out. The results of the study prove that communication services are the key to success in various businesses or activities that are service-based. Its role will be greater and decisive when in the activities of services in the community there is competition in an effort to seize the market or subscription. The quality of communication services in the Regional Library and Archives of Pandeglang Regency is very accepted by the surrounding community.Keywords : Service, communication, consistency, commitment, quality, qualitative